Effects of oral sialic acid on gut development, liver function and gut microbiota in mice. (5th April 2021) - Ma, J.; Gong, S.; He, Y.; Gao, W.; Hao, W.; Lan, X.
Abstract: Sialic acid (N‐acetylneuraminic acid), a 9‐carbon monosaccharide, has been widely studied in immunology, oncology and neurology. However, the effects of sialic acid on organ and intestinal development, liver function and gut microbiota were rarely studied. In this study, we found that oral sialic acid tended to increase the relative weight of liver and decreased the serum aspartate aminotransferase (GPT) activity. In addition, sialic acid treatment markedly reduced gut villus length, depth, the ratio of villus length/depth (L/D), areas, width and the number of goblet cells. Furthermore, gut microbes were changed in response to oral sialic acid, such as Staphylococcus lentus, Corynebacterium stationis, Corynebacterium urealyticum, Jeotgalibaca sp_PTS2502, Ignatzschineria indica, Sporosarcina pasteurii, Sporosarcina sp_HW10C2, Facklamia tabacinasalis, Oblitimonas alkaliphila, Erysipelatoclostridium ramosum, Blautia sp_YL58, Bacteroids thetaiotaomicron, Morganella morganii, Clostridioides difficile, Helicobacter tryphlonius, Clostridium sp_Clone47, Alistipes finegoldii, [pseudomonas]_geniculata and Pseudomonas parafulva at the species level. In conclusion, oral sialic acid altered the intestinal pathological state and microbial compositions, and the effect of sialic acid on host health should be further studied. Abstract : Significance and Impact of the Study: Sialic acid has been extensively studied in brain neurodevelopment, immunology and oncology, but the effects of sialic acid on host intestinal development, liver function and gut microbial compositions were rarely reported. In the current study, we found that oral sialic acid altered intestinal morphology and gut microbial compositions, which might further affect host health.